A Large-Scale Synthesis of α-Olefins and α,ω-Dienes - Kraus, George A.; Riley, Sean (Synthesis, 2012)
The decarbonylation of carboxylic acids or dicarboxylic acids in the presence of a palladium catalyst above 190 °C in the absence of a solvent constitutes a mild method for the large-scale synthesis of α-olefins and α,ω-dienes.
Keywords: alkene; decarbonylation; oxidative insertion; fatty acids; diene